Community Movement to Transform the Paradigm from Illegal Logger to Eco-lodger with a Dignity Oriented in Tangkahan Ecovillage - Sabam Syahputra Manurung; Furqan, Furqan; A.M. Hatuaon Sihite (Yayasan Literasi Sains Indonesia, 2025)
This research explores a community movement in Tangkahan Ecovillage, Indonesia, driven by a desire to safeguard their local ecology with dignity at the forefront. The study delves into the mechanisms and outcomes of this shift in approach through a case study, offering insights into community-driven efforts for sustainable forestry practices. It underscores the significance of grassroots movements in advocating for environmental conservation while prioritizing the well-being and respect of local residents. The movement seeks to transform people's perceptions by replacing destructive illegal logging with sustainable eco-logging methods. Through a case study methodology, the research investigates the motivations, strategies, and challenges faced by the community in this transformative process. By examining how the movement empowers the community and instills a sense of ownership over natural resources, the concept of dignity emerges as a central theme. The analysis of Tangkahan's journey in this study aims to provide a replicable model for transitioning from illegal-logging to eco-logging, promoting environmental sustainability and community welfare.